2014
DOI: 10.1182/blood.v124.21.79.79
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib, Lenalidomide, and Dexamethasone vs Lenalidomide and Dexamethasone in Patients (Pts) with Relapsed Multiple Myeloma: Interim Results from ASPIRE, a Randomized, Open-Label, Multicenter Phase 3 Study

Abstract: Background: Lenalidomide with dexamethasone (Rd) is a standard of care used for pts with relapsed multiple myeloma (RMM). The randomized, open-label, multicenter, phase 3 study ASPIRE (NCT01080391) is comparing carfilzomib, lenalidomide, and dexamethasone (KRd) to Rd in pts with RMM. The primary end point is progression-free survival (PFS; assessed by an independent review committee). Secondary end points include overall survival (OS), overall response rate (ORR), duration of response (DOR), health-related qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…No increase in overall toxicity was reported in the IXA group. Although addition of IXA to LEN and DEX resulted in a higher rate of peripheral neuropathy (27% versus 22% in the control group) [29], the incidence of grade 3 events was only 2% compared to 3% in patients who received CFZ [24] and 6% in those treated with subcutaneous BTZ [20]. This study led to the approval by the FDA of IXA in combination with [31].…”
Section: Bortezomibmentioning
confidence: 96%
See 4 more Smart Citations
“…No increase in overall toxicity was reported in the IXA group. Although addition of IXA to LEN and DEX resulted in a higher rate of peripheral neuropathy (27% versus 22% in the control group) [29], the incidence of grade 3 events was only 2% compared to 3% in patients who received CFZ [24] and 6% in those treated with subcutaneous BTZ [20]. This study led to the approval by the FDA of IXA in combination with [31].…”
Section: Bortezomibmentioning
confidence: 96%
“…Stewart et al reported the results of the randomized phase 3 ASPIRE trial, comparing the combination LEN, DEX and carfilzomib (CFZ) with that of LEN + DEX alone [24]. CFZ is a second-generation epoxyketone proteasome inhibitor, that binds selectively and irreversibly to the constitutive proteasome and immunoproteasome [24]. A series of 792 patients with relapsed MM after a median of two lines of treatment were randomized to receive one of the two combinations.…”
Section: Bortezomibmentioning
confidence: 99%
See 3 more Smart Citations